KUALITAS KRIOPRESERVASI SEMEN RUSA BAWEAN Axis kuhlii (Temminck, 1836) HASIL PENANGKARAN - Wirdateti Wirdateti; R Taufiq P Nugraha; G Semiadi; SK Widyastuti; Yulianto Yulianto (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Bawean Deer Axis kuhlii (Temminck, 1836) is an endemic deer species from Bawean island, Indonesia. Under the National Protection act, the species is listed as protected and in the IUCN is categorized as Critically Endangered. In order to maintain the existence of these species, wildlife conservation of germplasm is needed through development of technique of sperm cryopreservation for Bawean deer semen. The sperm were collected from captive animals in Station for Beef Cattle Research Center, Ministry of Agriculture, at Grati, Pasuruan, which consisted of two adult males and two sub-adult males. The research objective was to determine the quality and quantity of preserved sperm from captive deer Bawean in the form of frozen semen for conservation needs and further usage. Prior to sperm collections, the animal was anesthetized with mixture of xylazine and ketamin. Sperm was then collected by an electroejaculator using a 2-cm probe diameter and 17 cm of length. Extender solution used was tris glycerol. The semen was able to be collected only from two adult stags with sperm motility of 50-60% and sperm concentration was in the range of 500-1140 x 106sel/ml. This study suggested the need for monitoring the developmentof sperm in relation to antler development.